THE IMPACT OF THE WTO RETALIATION FROM THE PERSPECTIVE OF HUMAN RIGHTS LAW - Intan Innayatun Soeparna (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
World Trade Organization (WTO) dispute settlement system through Panel and Appellate Body, allows sanction to be imposed when a member is unwilling to bring a WTO-inconsistent trade measure into conformity. According to the Article 22 of Dispute Settlement Understanding (DSU), if in a certain case WTO Panel finds a party has failed to make new policy in compliance with the WTO rules, the aggrieved party is entitled to obtain retaliation. The WTO retaliation emerges negative impact for some countries in particular developing or small economic countries. This impact denotes the violation of international human rights law, particularly economic rights that stipulate in Universal Declaration of Human Rights (UDHR), International Covenant on Civil and Political Rights (ICCPR), and the International Covenant on Economic, Social and Cultural Rights (ICESCR). This paper explains the impact that arises when WTO retaliation is imposed to a country whether a developed or developing country, from the perspective of international human rights law.